Production of biodiesel using potassium hydroxide supported on alumina (KOH/AI203) / Nailul Amal Zakariah - Zakariah, Nailul Amal (2020)
In this study, waste cooking oil (WCO) was used to produce biodiesel using KOH supported onto alumina (KOH/AI203) as catalyst. Three parameters were studied to find the optimum conditions which are catalyst loading, reaction time and the reusability of the catalyst. AI203 was impregnated with KOH and characterized using thermogravimetric analyzer (TGA) before the catalyst was calcined at 7000°C for 3 hours. The reaction was refluxed with constant conditions at temperature of 65°C, 10% KOH-AI203, methanol to oil ratio of 12:1 for 3 hours. The reaction time was studied using optimum catalyst loading which is 7 wt.% catalyst amount and the reaction was varied from 1 hour - 4 hours reaction. The highest yield of biodiesel obtained was 73.7% in 2 hours of reaction. At the end of the study, the reusability of the catalyst was studied. 3 cycles of reaction was done using used catalyst from the previous reaction of 2 hours yield determination and found the decreasing pattern of yield after 4 cycles of reaction. Hence, the optimal conditions for this catalyst were reaction temperature at 65°C, 10% KOH-AI203, methanol to oil ratio of 12:1,7 wt.% catalyst loading at 2 hours reaction time with the highest yield of biodiesel is 73.7%.